Pericardial Effusion as a First Symptom of Thymoma: A Case Report - Suprit Malali; Sourya Acharya; Samarth Shukla; Sunil Kumar; Priti Mishra (Journal of Clinical and Diagnostic Research)
Thymomas, which account for 25% of all mediastinal tumours, primarily originate from the anterior mediastinum and tend to grow slowly, often being incidentally discovered during radiographic investigations. The clinical spectrum of thymoma ranges from asymptomatic incidental findings to the development of paraneoplastic syndromes and symptoms caused by local or metastatic involvement. Myasthenia Gravis symptoms may also be present, and in some cases, manifestations can arise due to pressure on adjacent structures. However, pericardial effusion as an initial and early presenting feature of thymoma remains extremely rare. In advanced and disseminated cases, pericardial and pleural effusions may occur. Therefore, it is crucial to consider the possibility of a concealed cardiac silhouette mimicking pericardial effusion in asymptomatic patients, ensuring a comprehensive evaluation. The current report represents a case study of a 56-year-old female patient with a history of subacute and progressive dyspnoea. Despite no significant positive clinical findings upon general and systemic examination, the diagnostic work-up revealed a modest pericardial effusion attributed to an unexpected thymoma. The present case highlights the unusual clinical manifestation, emphasises the diagnostic challenges involved, and underscores the importance of considering thymoma in the differential diagnosis of pericardial effusions.